The Impact of Asian Parliamentary Debate Techniques on the Arabic Speaking Skills of University Students: Penerapan Debat Parlementer Asia untuk Meningkatkan Kemampuan Berbicara Bahasa Arab di Perguruan Tinggi - Al Kautsar, Naafi; Mustofa, M. Tulus; Baroroh, Umi (Nady Al-Adab : Jurnal Bahasa Arab, 2025)
This study investigates the impact of Asian Parliamentary Debate (APD) techniques on the Arabic speaking skills of university students, specifically those in the Arabic Language Education program at UIN Sunan Kalijaga. Speaking skills, particularly in Arabic, are essential for students’ academic and professional success, yet many face challenges in mastering fluency, confidence, and argumentation. This research aims to evaluate the potential of APD in improving speaking skills, specifically fluency, self-confidence, and argumentative construction in Arabic. This qualitative study utilizes a descriptive methodology, incorporating observation, semi-structured interviews, and document analysis to collect data from second-semester students engaged in APD sessions. The study indicates notable advancements in students' speaking abilities, especially in areas of self-confidence, fluency, and argumentation. After three cycles of debate, students exhibited an increase in self-confidence from 60% to 90%, an improvement in fluency from 55% to 89%, and an enhancement in their ability to construct arguments from 50% to 90%. Furthermore, participation in debates also increased, from 60% to 95%. Interviews with students highlighted the positive effects of APD on overcoming public speaking fears and enhancing critical thinking. The findings suggest that APD techniques foster a dynamic and interactive learning environment that not only improves speaking skills but also boosts student engagement and critical thinking. These results contribute to the growing body of research on the effectiveness of debate techniques in language education, particularly in Arabic. The study recommends incorporating APD into Arabic language curricula to further enhance students' speaking abilities. Future research should explore the long-term effects of APD and its application in other language learning contexts